Evaluation of a Schema Therapy-based prevention group program for children and their parents - Roza Laious; Galanaki, Evangelia P.; Aikaterini Aggeli; Tzavara, Chara; Eftychia Argalia; Daria Bakourini; Vassiliki Koutrafouri; Aikaterini Marini; Ioanna Sintila (Journal of Evidence-Based Psychotherapies, 2024)
Although Schema Therapy has emerged as an effective treatment for a large range of psychopathology, there is limited research on its effectiveness with children and adolescents, especially for preventive purposes, in individual or group settings and with the involvement of parents. Therefore, the aim of this study was to conduct a preliminary evaluation of a newly developed group prevention program based on Schema Therapy (rationale, principles, and techniques) for children and their parents. It is a psychoeducational, developmentally-appropriate program addressing core emotional needs, early maladaptive schemas, schema modes, coping styles, and parent-child relationship with the aim of preventing the emergence of psychopathology in children. Participants were 90 Greek children (aged 9-13) who attended 16 weekly meetings and their parents who attended 10 biweekly meetings. The effectiveness of the program was evaluated with pre-and-post-intervention assessment (i.e., pre-experimental design). Children’s early maladaptive schemas (self-reports) and strengths and difficulties (self- and parent-reports), as well as parents’ early maladaptive schemas (self-reports) were assessed. Results showed a significant decrease in most early maladaptive schemas of children and in many early maladaptive schemas of parents. A significant decrease was found in children’s emotional symptoms, peer relationship problems and total difficulties score and a significant increase in prosocial behavior. The supporting evidence for the effectiveness of the program and the necessity of evidence-based prevention programs based on Schema Therapy for children and parents are discussed.